Performance Analysis of Unsignaled Intersection at Lawe Sigala-Gala of Intersection and Semadam Intersection, Southeast Aceh Regency - Deni Trianda Pitri (CERED Indonesia Institute, 2021)
Problem then cross often found in the city city big , for example city Kutacane . Problem congestion and chaos then cross often happened at the intersection roads , especially at intersections no signaled , the intersection of Jl. Lawe Sigala -gala and Simpang Goodbye Southeast Aceh District . This thing influenced by several factor that is the more increasing volume last traffic and the number of riders no obey regulations then cross . Analyze capacity and rate performance something deviation no signal so done data data from field , in the form of geometric data intersection ( width each leg of the intersection ), type and amount vehicles that cross intersection after multiplied with number equivalence from each _ vehicle , so obtained uniformity in unit car passenger (junior high school). Then calculated capacity and rate performance intersection that includes degrees boredom and procrastination deviation with method Manual of Indonesian Road Capacity 199 1 . Current then cross at the intersection Street lawe the biggest galaxies of the day Saturday of 311.25 SMP / hour . Current then cross at the intersection good luck biggest of the day Tuesday amounted to 292.27 SMP / hour . At the intersection lawe wolf score Degrees The biggest boredom is 0.161 ( DS <1) . At the intersection good luck Degrees The biggest boredom is 0.154 ( DS <1 ) . b based on DS Value shows that last volume cross on both intersection still under capacity basic requirements _ ie C 0 = 2700 smp /hour m. Congestion at the intersection _ Jl. Lawe Sigala -Gala and Simpang Goodbye Southeast Aceh Regency is caused by traders who use segment road and parking vehicles that do not regularly .